Reconstruction of Life Imprisonment in Prison System in Indonesia - Boma Wira Gumilar; Gunarto Gunarto; Akhmad Khisni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The most important part in a Book of Criminal Law (Penal Code) is a prison, because the prison contains rules about the size and implementation of the criminal. The position of life imprisonment in the national criminal justice system is still considered relevant as a means of crime prevention, it can be seen from the number of offenses punishable with life imprisonment. However, life imprisonment is considered contrary to the penal system. This study aims to investigate the implementation of life imprisonment, weaknesses, and the solution in the future. The approach used in the study is a non-doctrinal legal research with socio-legal research types (Juridical Sociological).The results of research studies show that life imprisonment is contrary to prison system, and life imprisonment become an obstacle to fostering convicts back into society. Bill Criminal Code of September 2019 can be used as a solution to life imprisonment change in the future. Presented advice, in order to be disseminated to the application of the criminal purpose of the Criminal Code of Prison adopted in the future, so that the public and experts no longer make the criminal as a form of retaliation.Keywords: Reconstruction; Crime; Prison; Life Imprisonment; System; Corrections.